Penerapan Konsep Earned Value Analysis terhadap Kinerja Biaya dan Waktu pada Proyek Pembangunan (Studi Kasus Proyek Pembangunan Gedung Terminal Pariwisata) - Purnomo, Dimas Aji ; Prisilia, Harliwanti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The development of construction projects is currently increasingly large and complex both in terms of physical and cost. In this case the project planning and control is applied to the construction of the Integrated Tourism Terminal Building which has a total price of Rp. 12,904,970,589.17 with a implementation period of 154 calendar days. One alternative that can be used in an effort to overcome the constraints on this project is the